Public transport towards sustainability in midsized municiplaities - Ribeiro, Paulo (2013)
Publicado em "Recent Advances in Engineering Mechanics, Structures and Urban Planning" (ISBN : 978-1-61804-165-4) ; Mathematics and Computers in Science and Engineering Series, 8 (ISSN : 2227-4588)